(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Vulvar cancer is a rare tumor accounting for <5% of female genital tract tumors. The most common type of vulvar malignancy is squamous cell carcinoma. There are many histological variants of squamous cell carcinoma, keratinizing type being the most common one. Sarcomatoid variant is an extremely rare variant in vulva and comprises both epithelial and mesenchymal features. Due to the rarity of this tumor in the vulva and limited cases reported in the literature, no proper management guidelines have been established yet. In the current case report, we describe a case of mixed warty and sarcomatoid squamous cell carcinoma of vulva.